Probing exciton properties and dynamics in lead halide perovskite semiconductors by optical spectroscopy - Do, Thi Thu Ha (Nanyang Technological University, 2020)
Lead halide perovskite semiconductors have emerged as potential building blocks for photovoltaic and optoelectronic applications. The rapid development of the low-cost synthesis methodologies and the continuous improvement of perovskite-based device efficiency have stimulated intensive research to unravel the behaviours of the photogenerated species, such as electrons, holes, coupled electron-hole pairs (excitons) and their interactions. The fundamental understanding of the electronic band structures and the interparticle coupling is still at its early stage. Several controversies among the experimental observations need to be resolved by both experimental and theoretical means.In this thesis, by utilizing steady-state and time-resolved optical spectroscopy, we investigate the exciton structures, linear and nonlinear optical properties and the effects of quantum-confinement on the optical responses of perovskite materials. Our systematic studies reveal that lead halide perovskites have complicated band structures with multiple states near the bandgap region, which are separated by only tens of milli-electron volts. As a result, multiple optical transitions occur to generate electron-hole pairs with different binding energies and properties. Under strong quantum-confinement regime, the spin-degeneracy of the exciton bands can be lifted due to the enhanced Coulomb interaction between electrons and holes that consequently produces exciton fine-structure. Particularly, in perovskite quantum-wells, we resolve the anisotropic excitons split by the anisotropic electron-hole exchange interaction, which, on the other hand, does not affect the spin-polarization of the indirect excitons. The interplay of different spin-interacting processes gives rise to the coexistence of anisotropic and isotropic excitons in twodimensional perovskites. Moreover, the exciton dynamics in low-dimensional structures is found to be faster due to the stronger interparticle interactions. The coupling between electrons and holes or electrons and phonons is also enhanced when further reducing the crystal dimensions into nanocrystal form leading to interesting phenomena. The electron-phonon and phonon-phonon interactions are found to be strong that are responsible for the phonon-assisted exciton transitions in perovskite nanocrystals. As a result, thermal energy can be efficiently extracted to produce light energy. Our results demonstrate that perovskite nanocrystals are ideal platforms for the energy conversion purposes. Our findings presented in this thesis provide deep insights into the exciton band structures and exciton fine-structure of perovskite materials. More questions are still to be solved in the future work to reconcile the discrepancy between experimental observations and theory. A unified understanding of the fundamental properties on this emergent class of semiconductors will pave the way towards exciton manipulation for novel device applications.